A Smartphone-based Decision Support Tool Improves Test Performance Concerning Application of the Guidelines for Managing Regional Anesthesia in the Patient Receiving Antithrombotic or Thrombolytic Therapy. (January 2016) - McEvoy, Matthew D.; Hand, William R.; Stiegler, Marjorie P.; DiLorenzo, Amy N.; Ehrenfeld, Jesse M.; Moran, Kenneth R.; Lekowski, Robert; Nunnally, Mark E.; Manning, Erin L.; Shi, Yaping; Shotwell, Matthew S.; Gupta, Rajnish K.; et al.
Abstract : Background: The American Society of Regional Anesthesia and Pain Medicine (ASRA) consensus statement on regional anesthesia in the patient receiving antithrombotic or thrombolytic therapy is the standard for evaluation and management of these patients. The authors hypothesized that an electronic decision support tool (eDST) would improve test performance compared with native physician behavior concerning the application of this guideline. Methods: Anesthesiology trainees and faculty at 8 institutions participated in a prospective, randomized trial in which they completed a 20-question test involving clinical scenarios related to the ASRA guidelines. The eDST group completed the test using an iOS app programmed to contain decision logic and content of the ASRA guidelines. The control group completed the test by using any resource in addition to the app. A generalized linear mixed-effects model was used to examine the effect of the intervention. Results: After obtaining institutional review board's approval and informed consent, 259 participants were enrolled and randomized (eDST = 122; control = 137). The mean score was 92.4 ± 6.6% in the eDST group and 68.0 ± 15.8% in the control group ( P < 0.001). eDST use increased the odds of selecting correct answers (7.8; 95% CI, 5.7 to 10.7). Most control group participants (63%) used some cognitive aid during the test, and they scored higher than those who tested from memory alone (76 ± 15% vs . 57 ± 18%, P < 0.001). There was no difference in time to completion of the test ( P = 0.15) and no effect of training level ( P = 0.56). Conclusions: eDST use improved application of the ASRA guidelines compared with the native clinician behavior in a testing environment. Abstract : In this multicenter, randomized trial of more than 250 residents and faculty, use of an electronic decision support tool improved adherence to guidelines in a testing environment regarding regional anesthesia and anticoagulation compared with a control group who could freely access the guidelines and any other cognitive aid.